Local flooding history affects plant recruitment in riparian zones. (15th March 2019) - Sarneel, Judith M.; Bejarano, Maria Dolores; van Oosterhout, Martin; Nilsson, Christer
Abstract: Aims: Many rivers across the globe are severely impacted by changed flooding regimes, resulting in drastic shifts in vegetation, but the processes driving the exchange of flood‐sensitive and flood‐tolerant species are understood less. We studied the role of long‐term and recent flooding histories for riparian plant recruitment in response to various changes in flooding regime. Location: Vindel River catchment (Northern Sweden). Methods: We experimentally changed long‐term flooding regimes by transplanting turfs between high and low elevations in 2000 and in 2014 ( n = 8 per treatment). We sowed seeds of five riparian species in both transplanted turfs and non‐transplanted controls and counted seedling numbers over two growing seasons. Further, we inventoried natural seedling frequencies in 190 plots in 19 reaches in 2013 and 2014, and related natural seedling numbers to plot flooding history in the period 2012–2014. Results: We observed effects of long‐term flooding history in the second year of the transplantation study (2015), but not in the first year. In 2015, turfs transplanted to locations with less flooding resulted in higher plant recruitment while transplantation to sites with more frequent flooding reduced recruitment compared to the controls. Since these differences were only found in recently transplanted turfs and not in older turfs, the legacy effect of long‐term flooding history can be transient. In the field seedling survey, similar differences were found between flooding‐history categories in 2013, but not in 2014, when the moisture conditions of the most recent year determined flooding. Further, lowest seedling numbers were observed when the previous flooding occurred in winter, and higher seedling numbers when floods occurred in spring or not at all. Conclusions: Both long‐term and recent flooding histories can affect plant recruitment, and their influence should be taken into account when designing restoration projects. Abstract : After reciprocal transplantation of turfs between riparian elevations, we found that germination decreased upon transplantation to low elevations (increased flooding) while germination was increased compared to the controls upon transplantation to high elevations (decreased flooding). These legacy effects were sometimes observed in a field survey, which further indicated the strong negative effect of historic winter flooding events.